Utilization of the C4.5 Algorithm for Classifying Students Who Are Eligible to Apply for Obtaining PIP - Fazira, Rizky Nazwa; Wanto, Anjar; Gunawan, Indra (Yayasan Literasi Sains Indonesia, 2023)
This research aims to optimize the selection process for eligible students for the Smart Indonesia Program (PIP) using the C4.5 algorithm. PIP is a social assistance program aimed at students who meet specific criteria. The C4.5 algorithm was chosen because it can produce a decision model that can be used to classify students based on various assessment factors. This study involved collecting student data based on predetermined PIP criteria. This data is then used as input to train the model using the C4.5 algorithm. The training involves identifying patterns and relationships between significant variables in determining a student's eligibility for PIP. This research resulted in a decision regarding PIP (Smart Indonesia Program) recipients with a low parental income classification who were entitled to assistance. It is hoped that the results of this research can contribute to increasing efficiency and accuracy in the selection process for PIP recipient students. Using the C4.5 algorithm is expected to produce more objective decisions and identify students who qualify for assistance more precisely. Apart from that, this research can also provide new insights regarding implementing algorithms in the context of education policy and social assistance.